Literary-Artistic and Folklore Onomastics: Common and Distinctive Features - (:unkn) unknown (Proceedings of the 27th International Congress of Onomastic Sciences. Onomastics in interaction with other branches of science. (Kraków, 22-27 August 2021), 2023)
The expansion of studies in literary onomastics and the accumulation of a considerable number of articles and monographs in the field proved the need to generalize the theoretical material. It also led to the extension and deepening of the subject of studies. It was not only the shift in linguistics priorities that contributed to the pursuit of new research objectives, but also the intensification of research, appearance of new extraordinary scholars and the inhomogeneity of appellative context including a variety of literary texts in which proper names have to function. Subsequently, the expansion of the scope of the analysed onyms in literary texts of different genres fostered the process of division into sub-fields of studies in literary onomastics. Today we can treat literary onomastics as a complex discipline that has already incor porated several sub-fields, including fiction, folklore, mythological and biblical onomastics. There are some interesting monographs on mythonyms and folklore onyms, as well as onyms in fiction and the Bible in Ukrainian onomastics. The purpose of the paper is to analyse the peculiarities of onyms used in fiction and folklore, as well as to describe the features and regularities that give reason to create a corpus of onymic data. The next step is to identify the specific features of literary onyms, to stress their special character, and to propose a suitable methodology.